The Decline of Nair Dominance : Society and Politics in Travancore 1847-1908 - Jeffrey,Robin
Century back the high caste families were mostly nairs, they held slaves they controlled lands concentrating in the southern princely states of Travancore. They were seen as landlords, the powerful lot, they were also known for the ill-treatment towards the lower caste people with arrogance and avoidance. This title is an effort to portray the much powerful air community during the 1847 as the book begins from that era to the decline of the much celebrated society. Women were provided the reference point for the control of property then and later the society crumbled due to many reasons which is examined in the title widely during the late nineteenth century, eaten away by the demands of a modernized state and ridiculed by foreign missionaries and Hindu critics from elsewhere.